Хроники “Гарабагнаме” по истории Гарабага - Бахышова Рена Ризван кызы (Культура народов Причерноморья, 2014)
Хроники "Гарабагнаме" об истории Карабаха "Гарабагнаме", который, как основной
источник имели большое значение для азербайджанской историографии в XIX - начале XX века ценным
источником для изучения не только истории Карабахского ханства, а также историю Азербайджана с
середины восемнадцатого и начале XIX века. Тем не менее, до недавнего времени, достижения истории
науки и ее возможностей, а также "Гарабагнаме" в течение длительного времени не не предметом
изучения, или не были объективно изучены.
"Гарабагнаме" является ценным источником для изучения политического, экономического и
культурного историю Карабахского ханства, его внешней политики, географии, этнографии, российско-
иранских отношений, а также отношений с Османской Турцией и Грузией. Хроніки "Карабахнаме" про історію Карабаху "Карабах Наме", який, як основне джерело
мали велике значення для азербайджанської історіографії в XIX - початку XX століття цінним
джерелом для вивчення не лише історії Карабаського ханства, а також історію Азербайджану з
середини вісімнадцятого і початку XIX століття . Тим не менш, до недавнього часу, досягнення історії
науки і її можливостей, а також "Гарабагнаме" протягом довгого часу не не предмет вивчення, або
були об'єктивно вивчені. "Гарабагнаме" є цінним джерелом для вивчення політичного, економічного та
культурного історію Карабаського ханства, його зовнішньої політики, географії, етнографії, російсько-
іранських відносин, а також відносин з Османською Туреччиною та Грузією. “Garabaghnamehs” which as the primary source were of great importance for Azerbaijan
historiography in the XIX - early XX century is a valuable source for studying not only history of the Garabagh
khanate as well as history of Azerbaijan from the mid of the XVIII and beginning of the XIX century. However,
until recently, the achievements of the history science and its features, as well as “Garabaghnameh” for a long
time have not been the subject of study, or have not been studied objectively. The authors of the works
"Garabagname" described in detail the historical geography, population, ethnic composition of the inhabitants
of Karabakh, the political events in Garabagh and neighboring regions, architectural monuments of the region,
new settlements created on the initiative of Karabakh Khans. All this information gives us an opportunity to
highlight the history, life, economic life, a number of features of the image of our people, to create a panorama
of fateful historical processes that took place in this region of Azerbaijan in the second half of the XVIII century.
“Garabaghnamehs” is a valuable source for studying the political, economic and cultural history of Garabagh
khanate, its foreign policy, geography, ethnography, the Russian-Iranian relations, as well as its relations with
Ottoman Turkey and Georgia.